2020
DOI: 10.3390/mi11030242
|View full text |Cite
|
Sign up to set email alerts
|

Core-Shell Beads Made by Composite Liquid Marble Technology as A Versatile Microreactor for Polymerase Chain Reaction

Abstract: Over the last three decades, the protocols and procedures of the DNA amplification technique, polymerase chain reaction (PCR), have been optimized and well developed. However, there have been no significant innovations in processes for sample dispersion for PCR that have reduced the amount of single-use or unrecyclable plastic waste produced. To address the issue of plastic waste, this paper reports the synthesis and successful use of a core-shell bead microreactor using photopolymerization of a composite liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…Our results show that 5 min blue light illumination did not cause severe effect on photobleaching of the PCR products due to the short exposure time and the protective shell. However, our previous studies [28,44] indicated that constant exposure on the sample during thermal cycling over a long period of time can cause photobleaching of amplicons. This issue was solved by non-continuous illumination on the beads during thermal cycling.…”
Section: Fabrication Of the Core-shell Beadmentioning
confidence: 98%
See 4 more Smart Citations
“…Our results show that 5 min blue light illumination did not cause severe effect on photobleaching of the PCR products due to the short exposure time and the protective shell. However, our previous studies [28,44] indicated that constant exposure on the sample during thermal cycling over a long period of time can cause photobleaching of amplicons. This issue was solved by non-continuous illumination on the beads during thermal cycling.…”
Section: Fabrication Of the Core-shell Beadmentioning
confidence: 98%
“…The synthesis and characterization of a core-shell bead was reported previously [44]. The synthesis of the bead consists of four main steps.…”
Section: Fabrication Of the Core-shell Beadmentioning
confidence: 99%
See 3 more Smart Citations